Phytochemical drug candidates for the modulation of peroxisome proliferator‐activated receptor γ in inflammatory bowel diseases. (3rd February 2020) - Venkataraman, Balaji; Ojha, Shreesh; Belur, Prasanna D.; Bhongade, Bhoomendra; Raj, Vishnu; Collin, Peter D.; Adrian, Thomas E.; Subramanya, Sandeep B.
Abstract : Plant‐based compounds or phytochemicals such as alkaloids, glycosides, flavonoids, volatile oils, tannins, resins, and polyphenols have been used extensively in traditional medicine for centuries and more recently in Western alternative medicine. Extensive evidence suggests that consumption of dietary polyphenolic compounds lowers the risk of inflammatory diseases. The anti‐inflammatory properties of several phytochemicals are mediated through ligand‐inducible peroxisome proliferator‐activated receptors (PPARs), particularly the PPARγ transcription factor. Inflammatory bowel disease (IBD) is represented by ulcerative colitis, which occurs in the mucosa of the colon and rectum, and Crohn's disease (CD) that can involve any segment of gastrointestinal tract. Because of the lack of cost‐effective pharmaceutical treatment options, many IBD patients seek and use alternative and unconventional therapies to alleviate their symptoms. PPARγ plays a role in the inhibition of inflammatory cytokine expression and activation of anti‐inflammatory immune cells. The phytochemicals reported here are ligands that activate PPAR γ, which in turn modulates inflammatory responses. PPARγ is highly expressed in the gut making it a potential therapeutic target for IBDs. This review summarizes the effects of the currently published phytochemicals that modulate the PPAR γ pathway and reduce or eliminate colonic inflammation.